Quite time longitudinal and UT variation of the equatorial electrojet inferred from CHAMP satellite (2010)
Analysis of the longitudinal and UT variations of the height integrated eastward current intensity of the equatorial electrojet in the solar maximum and solar minimum years (2002) and (2006) using CHAMP Satellite data is presented here. The low orbit of the CHAMP and its high precision instrumentation makes it suitable for the study. Data were selected from the hours of 10 to 13 around local noon and during magnetically quiet periods when the equatorial electrojet was expected to be highest. The results obtained showed that the amplitudes of the longitudinal variation were higher in the solar maximum year than in the solar minimum year and the regularities and irregularities in the longitudinal variations were almost the same in both the solar maximum and solar minimum years. Similarly, the regularities and irregularities in the Universal time (UT) variations were almost the same in both years. We observed that the systematic and unsystematic variations of the EEJ with longitudes and UT were not affected by the solar activity.